ERASMUS, R.P.B. Inventory of documents - ERASMUS, R.P.B. (ARCA, 2018)
Private papers of Judge R.P.B. Erasmus, Chairman of the Erasmus Commission.
COVERAGE 1922-1984; 67 Files; 2,00 Metres. AUDIO CASSETTES IN ARCA COLLECTION = 10
Keywords: ERASMUS, R.P.B.; Erasmus Commission